The Philosophy of Nishida Kitarō - Smith, Broderick (My University, 2025)
In this paper, I will examine the philosophy of Japan’s premier philosopher of the twentieth century, Nishida Kitarō (1870-1945). Born in the Meiji period of Japanese history, in which Japan opened to Western ideas, Nishida was the first to combine Western philosophy with East Asian ideas, especially the Zen Buddhist concept of Nothingness. Nishida’s philosophy, especially his “Logic of Place” (basho no ronri), has had a significant impact on Japanese philosophy, especially that of the “Kyōto School of Philosophy.” Despite his importance in Japanese philosophy, as well as the extent to which he was able to combine East Asian and Western ideas, Nishida is not widely discussed by Western academics, students of Japan, and researchers on global philosophy. As a corrective, this paper aims to explain Nishida’s philosophy, address the impact it had during his years as a professor of philosophy at Kyōto Imperial University, in the decades that followed his retirement, and up to the present, as well as how Nishida's philosophy remains relevant in the twenty-first century and beyond.
Keywords: Nishida Kitarō; Philosophy; Kyoto School Philosophy